Pulmonary arterial hypertension - progress in understanding the disease and prioritizing strategies for drug development - Ghataorhe,P; Rhodes,CJ; Harbaum,L; Attard,M; Wharton,J; Wilkins,MR (Journal of Internal Medicine, 2017)
Pulmonary arterial hypertension (PAH), at one time a largely overlooked disease, is now the subject of intense study in many academic and biotech groups. The availability of new treatments has increased awareness of the condition. This in turn has driven a change in the demographics of PAH, with an increase in the mean age at diagnosis. The diagnosis of PAH in more elderly patients has highlighted the need for careful phenotyping of patients and for further studies to understand how best to manage pulmonary hypertension associated with, for example, left heart disease. The breadth and depth of expertise focused on unravelling the molecular pathology of PAH has yielded novel insights, including the role of growth factors, inflammation and metabolic remodelling. The description of the genetic architecture of PAH is accelerating in parallel, with novel variants, such as those reported in potassium two-pore domain channel subfamily K member 3 (KCNK3), adding to the list of more established mutations in genes associated with bone morphogenetic protein receptor type 2 (BMPR2) signalling. These insights have supported a paradigm shift in treatment strategies away from simply addressing the imbalance of vasoactive mediators observed in PAH towards tackling more directly the structural remodelling of the pulmonary vasculature. Here, we summarize the changing clinical and molecular landscape of PAH. We highlight novel drug therapies that are in various stages of clinical development, targeting for example cell proliferation, metabolic, inflammatory/immune and BMPR2 dysfunction, and the challenges around developing these treatments. We argue that advances in the treatment of PAH will come through deep molecular phenotyping with the integration of clinical, genomic, transcriptomic, proteomic and metabolomic information in large populations of patients through international collaboration. This approach provides the best opportunity for identifying key signalling pathways, both a